1996
DOI: 10.1002/(sici)1099-0801(199603)10:2<60::aid-bmc559>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Fenitrothion in Soil

Abstract: The biodegradation of fenitrothion (an organophosphorus pesticide) in garden soil of western Uttar Pradesh in northern India has been studied. Both natural and autoclaved soil were treated with 10 p.p.m. of fenitrothion at field capacity moisture and incubated for 90 days in glass containers at 25 and 40°C. The soil samples were collected at various intervals between 0 and 90 days and analysed by HPLC for the residual pesticide and metabolites formed. At 0 days the recovery of the pesticide was 98% and the pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…O, O-dimethyl-O-(3-methyl-4-amino) phosphate, formed by oxidation of the S atom with O in aminofenitrothion. Although direct oxidation of fenitrothion into fenitroxon has been reported in T. mossambica (Anjum and Qadri, 1986), in rainbow trout (Kanazawa, 1975), in Cyprinus carpio (Miyamoto et al, 1979) and in soil (Roy et al, 1996), our kinetic data favours formation of oxon through metabolite I. However, Kojima et al (1989) reported aminofenitrothion, amino-…”
Section: Characterization Of Metabolite By Infrared Spectroscopycontrasting
confidence: 52%
“…O, O-dimethyl-O-(3-methyl-4-amino) phosphate, formed by oxidation of the S atom with O in aminofenitrothion. Although direct oxidation of fenitrothion into fenitroxon has been reported in T. mossambica (Anjum and Qadri, 1986), in rainbow trout (Kanazawa, 1975), in Cyprinus carpio (Miyamoto et al, 1979) and in soil (Roy et al, 1996), our kinetic data favours formation of oxon through metabolite I. However, Kojima et al (1989) reported aminofenitrothion, amino-…”
Section: Characterization Of Metabolite By Infrared Spectroscopycontrasting
confidence: 52%
“…Some degradation products of the pesticides considered here in various matrices have been described. For fenitrothion, many compounds have been identified and studied in soil, urine and water;2–7 a summary of the microbial metabolites and their mutagenicity has also been published 8. With respect to the dicarboximides vinclozoline and procymidone, 3,5‐dichloroaniline is often cited as a degradation product in water, plants, must and wine 9–13.…”
mentioning
confidence: 99%
“…In addition, the lowest residue level of thiobencarb was detected at 84 th day (0.24 µg/g soil, 0.36% of the initial residue remaining). It was found that the pesticide degraded linearly with incubation time (Roy et al, 1996). Our results indicated that the dissipation rate of thiobencarb from the tested soil was greater than fenitrothion at the intial 5 day after treatment.…”
Section: Dissipation Of Fenitrothion and Thiobencarb In Soilmentioning
confidence: 56%